PERTIMBANGAN HAKIM DALAM MENJATUHKAN PIDANA PENJARA 1 TAHUN TERHADAP PELAKU TINDAK PIDANA YANG TERBUKTI SECARA SAH DAN MEYAKINKAN TELAH MELAKUKAN PENGGELAPAN KARENA HUBUNGAN KERJA (Studi Putusan Nomor: 268/Pid.B/2022/PN.Tjk) - I Ketut Siregig; Ansori Ansori; Febri Anggraini (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2022)
The Criminal Code in Indonesia has regulated criminal acts and criminal sanctions, according to the crimes or violations committed. One of the most common crimes is embezzlement. Embezzlement is an act of dishonesty by hiding other people's goods/assets by one or more people without the knowledge of the owner of the goods with the aim of controlling, or using it for other purposes. This article discusses the crime of embezzlement, especially regarding the crime of embezzlement in work relations and the judge's considerations in making a decision on the crime of embezzlement in the work relationship. The research method used is normative and empirical. embezzlement by using a position contained in Article 374 of the Criminal Code which is an aggravated form of embezzlement, the meaning is that the elements of embezzlement in the main form have been fulfilled plus elements that are burdensome for the perpetrator. The aggravating factors for the perpetrator were based on the greater trust given to the person in control of the embezzled object. Several types of giving trust are used as problems that give rise to embezzlement in the main form, namely the relationship between the perpetrator who is given the trust and the victim who gives the trust.